2008
DOI: 10.4314/eamj.v85i7.9649
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Virus and its genotypes among a cohort of drug users in Kenya

Abstract: Prevalence of hePatitis c virus and its genotyPes among a cohort of drug users in KenyaConclusions: these results demonstrate a high hcv infection prevalence among this cohort of drug users (22.2 %) as compared to that of the general population, which is estimated to be 0.2-0.9%. The study also confirms the presence of at least two major genotypes among Kenyan drug users (genotypes 1 and 4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 4 publications
10
20
0
Order By: Relevance
“…This findings relate to data from a study done on the prevalence of HCV and its genotypes among a cohort of drug users in Kenya which estimates the prevalence in the general population to be between 0.2%-0.9% [20]. Much higher rates of 22.2% and 17.5% are also reported in other studies in Kenya [19], and Egypt [21].…”
Section: Discussionsupporting
confidence: 73%
“…This findings relate to data from a study done on the prevalence of HCV and its genotypes among a cohort of drug users in Kenya which estimates the prevalence in the general population to be between 0.2%-0.9% [20]. Much higher rates of 22.2% and 17.5% are also reported in other studies in Kenya [19], and Egypt [21].…”
Section: Discussionsupporting
confidence: 73%
“…This result corresponds well with that of a previous study of Korean injecting drug users [Yun et al, 2008] as well as in patients with HCV-related chronic liver disease in Korea [Suh and Jeong, 2006]. In other countries, genotype 1a [Beld et al, 1998;Muasya et al, 2008;Novais et al, 2009] or 3a [Kalinina et al, 2001;Micalessi et al, 2008;Sereno et al, 2009;Demetriou et al, 2010;Mehta et al, 2010;Ciccozzi et al, 2011] were reported as the most common genotype among injecting drug users. With regard to the treatment outcome, genotype 1 is generally associated with lower rates of the complete eradication with interferon a therapy [Scott and Gretch, 2007].…”
Section: Discussionsupporting
confidence: 90%
“…The highest HCV seroprevalence estimate identifi ed was recorded in Kenya in a sample population of 145 injecting drug users (46% with HCV). 22 By contrast, analysis of the 20 liver disease cohorts showed an overall pooled HCV seroprevalence estimate of 9·95% (fi gure 3, appendix). Although estimated levels of infection were similar in west and southeast Africa, in the central region the pooled seroprevalence of HCV in liver disease cohorts was 2·5% (fi gure 3).…”
Section: Resultsmentioning
confidence: 96%